Role of Al in Na-ZSM-5 zeolite structure on catalyst stability in butene cracking reaction - Auepattana-aumrung, Chanon (Sci Rep, 2020)
The Na-ZSM-5 catalysts (SiO(2)/Al(2)O(3) molar ratio = 20, 35, and 50) were prepared by rapid crystallization method to investigate their performance in butene cracking reaction. The XRD, XRF, NH(3)-TPD, FT-IR, TPO, UV–Vis, and (1)H, (27)Al, (29)Si MAS NMR techniques were used to identify the physical and chemical properties of Na-ZSM-5 catalysts. The silanol group (Si–OH) was the main acid site of Na-ZSM-5, and it was proposed to be the active site for the butene cracking reaction. The butene conversion and coke formation were associated with the abundance of silanol groups over the Na-ZSM-5 catalyst. The dealumination, resulting in the deformation of tetrahedral framework aluminum species was a key factor for Na-ZSM-5 catalyst deactivation, because of the Si–O–Al bond breaking and formation of Si–O–Si bond. The stability of the Si–O–Al bond was linked to the molar number of sodium since the Na atom interacts with the Si–O–Al bond to form Si–ONa–Al structure, which enhances the stability of the silanol group. Therefore, the Si–ONa–Al in zeolite framework was an essential structure to retain the catalyst stability during the reaction. The Na-ZSM-5 with the lowest SiO(2)/Al(2)O(3) molar ratio showed the best performance in this study resulting the highest propylene yield and catalyst stability.